PENYIMPANGAN PERILAKU SEKSUAL (MENELAAH MARAKNYA FENOMENA LGBT DI INDONESIA) - Elbina Mamla Saidah (STAI Hubbulwathan Duri, 2016)
The phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) makes people very worried. Pros and cons of the LGBT happen in the mass media; print media and electronic media. In medical science, there are four major categories of mental disorder diagnosis, namely: gender identity disorder, sexual deviation, psychosexual dysfunction, and other psychosexual disorders such as homosexuals. The LGBT issue should get a good handle on all aspect, especially the family. Parenting and monitoring the development of children from infancy to adolescence need to be improved so that children develop well.